PENGARUH MACAM DAN WAKTU APLIKASI FUNGISIDA NABATI TERHADAP PERKEMBANGAN PENYAKIT ANTRAKNOSA PADA PISANG LEPAS PANEN THE EFFECT OF KINDS AND APPLICATION TIME OF BOTANICAL FUNGICIDES ON ANTHRACNOSE DEVELOPMENT OF POSTHARVEST BANANA - Angkat, Suka Edah; Soesanto, Loekas; Pramono, Eko (Pembangunan Pedesaan, 2006)
Research aimed at knowing kinds, concentration, and application time of botanical fungicides on development of anthracnose in vitro and in vivo, and organoleptic test on postharvest banana. The in vitro test was arranged by factorial based on Completely Randomized Design with kinds of the fungicides, i.e., leaves extract of neem, soursop, or pepper betle as the first factor and concentration as the second one. The in vivo one was designed with Split-Split Plot Design, as main plot, subplot, and sub-subplot were kinds of the fungicides, injury or inoculation, and application time, respectively. Result of the research pointed out that leaves extract of pepper betle 30% had the same ability to suppress anthracnose fungus in vitro with benomyl. However, the leaves extract of neem 30% given before injury or inoculation was the best treatment to decrease the disease as 63.13%. The botanical fungicides did not affect aroma, color, and taste of banana.